2017
DOI: 10.18632/oncotarget.17469
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate leads to necrosis and apoptosis in hepatocellular carcinoma cells via inhibition of glycolysis and represses tumor growth in mice

Abstract: Methyl jasmonate has recently been found to have anti-cancer activity. Methyl jasmonate detached hexokinase 2 from a voltage dependent anion channel causing a reduction in mitochondrial transmembrane potential that led to the release of cytochrome C and apoptosis inducing factor resulting in intrinsic apoptosis. Blocked adenosine triphosphate synthesis caused by mitochondrial injury hampered oxidative phosphorylation and led to cell necrosis. The results were applied to the in vivo treatment of nude mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 46 publications
4
31
3
Order By: Relevance
“…This conclusion was consistent with the results of Sumi et al' [44] and Ding et al' [32], showing that glycolysis and apoptosis of cells could be improved simultaneously. But it was not in agreement with the ndings of Li et al' [43] and Comin-Anduix et al' [40], who showing that glycolysis of cells was inhibited and apoptosis of cells was enhanced, possible owing to differences in the type of cell. Glycolysis is the main source of energy in cancer cells, which use this metabolic pathway for ATP generation.…”
Section: Discussioncontrasting
confidence: 68%
“…This conclusion was consistent with the results of Sumi et al' [44] and Ding et al' [32], showing that glycolysis and apoptosis of cells could be improved simultaneously. But it was not in agreement with the ndings of Li et al' [43] and Comin-Anduix et al' [40], who showing that glycolysis of cells was inhibited and apoptosis of cells was enhanced, possible owing to differences in the type of cell. Glycolysis is the main source of energy in cancer cells, which use this metabolic pathway for ATP generation.…”
Section: Discussioncontrasting
confidence: 68%
“…MeJA's cytotoxic activity against cancer cells is reported to occur as consequence of one or more of the following events: (I) increased ROS production in mitochondria of cancer cells, which are more sensitive than normal cells to higher ROS concentrations [ 2 ], and (II) modification of the mitochondrial respiration of cancer cells which provokes ATP depletion [ 1 ]; and (III) impaired glucose metabolism through glycolysis, due to hexokinase inhibition [ 50 ]. The results of this study show that hepatic cells of both healthy and arthritic rats respond to MeJA, at least partly, in the same way as cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion was consistent with Sumi's [42] and Ding's [33] results that both glycolysis and apoptosis of cells could be improved. It was contradict with Li's [41] and Comin-Anduix's [38] results that glycolysis of cells was inhibited and apoptosis of cells was enhanced. There may be the mainly reason is the type of cell.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, There has shown that the glycolysis could be inhibited and the cell apoptosis was further blocked [40]. Li found that methyl jasmonate could inhibit the glycolysis and induce apoptosis of tumor cells [41]. Sumi found that propofol could improve glycolysis of cells and lead to the apoptosis of cells [42].…”
Section: Discussionmentioning
confidence: 99%